2019
DOI: 10.1002/anie.201909424
|View full text |Cite
|
Sign up to set email alerts
|

Supported Catalytically Active Supramolecular Hydrogels for Continuous Flow Chemistry

Abstract: Inspired by biology, one current goal in supramolecular chemistry is to control the emergence of new functionalities arising from the self‐assembly of molecules. In particular, some peptides can self‐assemble and generate exceptionally catalytically active fibrous networks able to underpin hydrogels. Unfortunately, the mechanical fragility of these materials is incompatible with process developments, relaying this exciting field to academic curiosity. Here, we show that this drawback can be circumvented by enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Self-Assembly of Peptide HC atalyzes the Production of Hb y Hydrolysis of the Precursor HE 2 Recently we have shown that heptapeptides H,t hat is, Fmoc-GFFYGHY,e xhibit ac atalytic activity when they are self-assembled resulting in hydrogel formation that efficiently catalyzes the hydrolysis of al arge panel of non-activated esters, [23] af eature barely reported in the literature for selfassembled catalytic systems. [28][29][30][31][32] Indeed, all classes of ester are catalytically transformed into their corresponding carboxylic acid by using this catalytically active supramolecular hydrogel (CASH).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Self-Assembly of Peptide HC atalyzes the Production of Hb y Hydrolysis of the Precursor HE 2 Recently we have shown that heptapeptides H,t hat is, Fmoc-GFFYGHY,e xhibit ac atalytic activity when they are self-assembled resulting in hydrogel formation that efficiently catalyzes the hydrolysis of al arge panel of non-activated esters, [23] af eature barely reported in the literature for selfassembled catalytic systems. [28][29][30][31][32] Indeed, all classes of ester are catalytically transformed into their corresponding carboxylic acid by using this catalytically active supramolecular hydrogel (CASH).…”
Section: Resultsmentioning
confidence: 99%
“…HP 2 is aw ater-soluble peptide that does not self-assemble and exhibits no catalytic activity.T he amount of H peptide released from HP 2 can be tuned by using AP because this enzymatic action allows acomplete generation of H.W ethus mixed HP 2 , AP,and HE 2 by keeping the concentration of HE 2 constant at 7.6 mm and by decreasing the concentrations of both HP 2 and AP from 790, 79, 7.9, 0.79 mm and 5.9, 0.59, 0.059, 0.0059 mm, respectively.W efollowed the conversion of HE 2 into H over time by HPLC (Figures 2a and S2). A concentration of 10 mg mL À1 for HE 2 was chosen because it corresponds to the critical gelation concentration (CGC) of H. [23] In all cases,t he in situ generation of H is formed with decreasing kinetics when the concentrations of AP and HP 2 are reduced:f or the lower concentration of AP and HP 2 , The precursor HP 2 is enzymatically dephosphorylated by AP leading to the self-assembly of the hydrogelator H.F rom the resulting assembly emerges an esterase-like activity efficient enough to hydrolyze HE 2 into H,s elf-sustaining the growth of the catalytic material.…”
Section: Autocatalytic Hydrogel Growth Initiated By An Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…HP 2 is aw ater-soluble peptide that does not self-assemble and exhibits no catalytic activity.T he amount of H peptide released from HP 2 can be tuned by using AP because this enzymatic action allows acomplete generation of H.W ethus mixed HP 2 , AP,and HE 2 by keeping the concentration of HE 2 constant at 7.6 mm and by decreasing the concentrations of both HP 2 and AP from 790, 79, 7.9, 0.79 mm and 5.9, 0.59, 0.059, 0.0059 mm, respectively.W efollowed the conversion of HE 2 into H over time by HPLC (Figures 2a and S2). A concentration of 10 mg mL À1 for HE 2 was chosen because it corresponds to the critical gelation concentration (CGC) of H. [23] In all cases,t he in situ generation of H is formed with decreasing kinetics when the concentrations of AP and HP 2 are reduced:f or the lower concentration of AP and HP 2 , The precursor HP 2 is enzymatically dephosphorylated by AP leading to the self-assembly of the hydrogelator H.F rom the resulting assembly emerges an esterase-like activity efficient enough to hydrolyze HE 2 into H,s elf-sustaining the growth of the catalytic material. Angewandte Chemie (5.9 nm and 0.79 mm, respectively), the transformation of HE 2 into H starts significantly after 27 hours and then the transformation accelerates in asimilar manner to anucleation and growth process (Figure 2a).…”
Section: Autocatalytic Hydrogel Growth Initiated By An Enzymementioning
confidence: 99%